2021
DOI: 10.3389/fmars.2021.677732
|View full text |Cite
|
Sign up to set email alerts
|

Meroplankton Diversity, Seasonality and Life-History Traits Across the Barents Sea Polar Front Revealed by High-Throughput DNA Barcoding

Abstract: In many species of marine benthic invertebrates, a planktonic larval phase plays a critical role in dispersal. Very little is known about the larval biology of most species, however, in part because species identification has historically been hindered by the microscopic size and morphological similarity among related taxa. This study aimed to determine the taxonomic composition and seasonal distribution of meroplankton in the Barents Sea, across the Polar Front. We collected meroplankton during five time poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 108 publications
1
21
0
Order By: Relevance
“…The two passive fronts of the investigated area have maintained distinct communities of the GZ (Figures 5, 6), in that a portion of taxa were unique for a particular frontal zone, but the few, most abundant ones, were common everywhere. Previous studies from the region arrived at a similar conclusion, like Descôteaux et al (2021) who found that only one-third of meroplankton were shared among both sides of the PF. In any other place in the world's ocean, the presence of the same taxa on both sides of the front would lead to the conclusion of the GZ community exchange across the passive fronts.…”
Section: Discussionsupporting
confidence: 70%
“…The two passive fronts of the investigated area have maintained distinct communities of the GZ (Figures 5, 6), in that a portion of taxa were unique for a particular frontal zone, but the few, most abundant ones, were common everywhere. Previous studies from the region arrived at a similar conclusion, like Descôteaux et al (2021) who found that only one-third of meroplankton were shared among both sides of the PF. In any other place in the world's ocean, the presence of the same taxa on both sides of the front would lead to the conclusion of the GZ community exchange across the passive fronts.…”
Section: Discussionsupporting
confidence: 70%
“…For some, the dispersal stage is short, lasting from minutes to a few hours and resulting largely in recruitment to the parent population, while others disperse for up to several months (Shanks 2009) and, in rare cases, years (Strathmann & Strathmann 2007). In a previous seasonal study in the Barents Sea, most meroplanktonic taxa were found at discrete time points suggesting a larval phase of no more than a few months, though a minority of taxa showed evidence of longer dispersal periods (though still shorter than a year; Descôteaux et al 2021). Those taxa with the potential for longdistance dispersal may be better adapted to finding new habitat following periods of change (Wares & Cunningham 2001, Hardy et al 2011.…”
Section: Introductionmentioning
confidence: 90%
“…Such a strategy relies on species-level identification of larvae, which has historically been challenging because of the general lack of speciesspecific features at the larval stage for most taxa. New molecular methods, however, now enable reliable identification of planktonic early life stages of benthic invertebrates (Ershova et al 2019, Descôteaux et al 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the morphological identification of meroplankton is very time-consuming and labor-intensive even for experienced taxonomists (Ershova et al, 2021;Pappalardo et al, 2021). In recent years, with a rapid growth in the number of reference barcodes in public databases as well as the advances in methods specifically designed to barcode meroplankton (Ershova et al, 2019), describing meroplankton into lower taxonomic level has become feasible (Hebert et al, 2003;Descoteaux et al, 2021).…”
Section: Introductionmentioning
confidence: 99%